2016
DOI: 10.15376/biores.11.2.3598-3613
|View full text |Cite
|
Sign up to set email alerts
|

Soft Sensors for Pulp Freeness and Outlet Consistency Estimation in the Alkaline Peroxide Mechanical Pulping (APMP) High-Consistency Refining Process

Abstract: In the mechanical pulping process, some process state and product quality variables are difficult to measure on-line. In this paper, soft sensors were used to estimate Canadian Standard Freeness (CSF) and outlet consistency (Cout) after the high consistency refining stage of the alkaline peroxide mechanical pulping (APMP) process. After the secondary variables for modeling that are readily available processed measurements in pre-treatment and the HC refining stage was selected, models based on the case-based r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Those conditions have been reported to cause poor pulp quality (Miles and May 1989), and it was shown in this study that temperature peak and fiber cutting are linked together. The pulp quality control systems using soft sensors can be improved (Zhang et al 2016;Karlström and Hill 2018). Additionally, by using the knowledgeand with the help of sophisticated control loops mills can increase the bonding potential of the pulp by avoiding the fiber cutting tendency.…”
Section: Discussionmentioning
confidence: 99%
“…Those conditions have been reported to cause poor pulp quality (Miles and May 1989), and it was shown in this study that temperature peak and fiber cutting are linked together. The pulp quality control systems using soft sensors can be improved (Zhang et al 2016;Karlström and Hill 2018). Additionally, by using the knowledgeand with the help of sophisticated control loops mills can increase the bonding potential of the pulp by avoiding the fiber cutting tendency.…”
Section: Discussionmentioning
confidence: 99%
“…If this scenario is present, a soft sensor can potentially be used to calculate quantities based on interaction from multiple signals. Zhang et al (2016) developed a soft sensor for estimating freeness and outlet consistency according to a case-based reasoning method based on operating conditions and pulp quality data. One of the conclusions in the study was that real-time soft sensors estimating freeness and outlet consistency can support reducing the electricity consumption and maintain uniform pulp quality.…”
Section: Previous Studies On Mechanical Pulp Modellingmentioning
confidence: 99%
“…And then I thought about an article that we recently published: Zhang et al (2016) showed that it is possible to gain an improved understanding of the functional relationship between different process variables just by looking at routine process data, without any "mill trial" activity at all. Often there is enough random variation in such data to be able to train an artificial intelligence algorithm.…”
Section: Roots Of Our Curiositymentioning
confidence: 99%